The use of surface electromyography for the study of auricular acupuncture - Politti, Fabiano; Amorim, Cesar Ferreira [UNESP]; Calili, Lilian; de Oliveira Andrade, Adriano; Palomari, Evanisi T. (Elsevier, 2010)
The advancement of knowledge in neurophysiology has demonstrated that acupuncture is a method of peripheral neural stimulation that promotes local and systemic reflexive responses. The purpose of this study was to determine if surface electromyography can be used as a tool to study the action of auricular acupuncture on striated skeletal muscle. The electromyographic amplitudes of the anterior, middle and posterior deltoid muscle and the upper trapezium muscle with 20%, 40% and 60% of maximal voluntary contraction of 15 healthy volunteers, were analyzed after the individuals were submitted to the auricular acupuncture treatment. The non-parametric Friedman test was used to compare Root Mean Square values estimated by using a 200 ms moving window. Significant results were further analyzed using the Wilcoxon signed rank test. In this exploratory study, the level of significance of each comparison was set to p < 0.05. It was concluded in this study that a surface electromyography can be used as a tool to investigate possible alterations of electrical activity in muscles after auricular acupuncture. However there is still a lack of adequate methodology for its use in this type of study, being that the method used to record the electromyographic signal can also influence the results. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Auricular acupuncture; Electromyography; Neurophysiology; acupuncture; adult; clinical article; deltoid muscle; ear cartilage; electric activity; electromyography; female; Friedman test; human; male; methodology; muscle contraction; neurophysiology; normal human; reflex; signal transduction; skeletal muscle; trapezium bone; Acupuncture, Ear; Adult; Female; Humans; Male; Muscle, Skeletal; Statistics, Nonparametric; Young Adult